Implementation of Digital Zakat Payments at the National Amil Zakat Agency (BAZNAS) of Bandung City - Muhammad Istajib Munajat; Jimi Malik Bin Algiani; Muhammad Sahrul Roihansyah; Jaenudin J; Dian Herdiana (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to examine the implementation of digitalization in the zakat payment system at BAZNAS Bandung City and its impact on management efficiency and community engagement. The rationale behind this investigation stems from the necessity for zakat organizations to embrace technological advancements to enhance transparency, accountability, and service accessibility. The methodology used is qualitatively descriptive, involving interviews, observations, and documentation from BAZNAS stakeholders and digital service users. The findings indicate that the deployment of the BAZNAS Digital Office framework and additional digital platforms has facilitated zakat payments, expanded the scope of collection, and improved transparency in distribution processes. Moreover, digitalization has encouraged the involvement of non-civil servant communities in consistent and effective zakat practices. Nevertheless, challenges remain, including limited digital literacy, technical malfunctions, and concerns regarding data security. In summary, the digital transformation of zakat at BAZNAS Bandung City represents a significant step toward contemporary, efficient, and accountable zakat administration. Enhancing human resource capacity and system security is crucial to maintaining public trust. Practically, this study underscores the importance of collaboration between zakat institutions and the technology sector to strengthen the social impact of zakat in the digital era.